Kontekstualisasi Nilai-Nilai Pancasila dan Hadis dalam Merespon Fenomena LGBT (Lesbian, Gay, Bisexual, dan Transgender) - Sarmida Hanum; Muhammad Sabri (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2023)
This study aims to contextualize the values of Pancasila and Hadith in responding to the phenomenon of LGBT (Lesbian, Gay, Bisexual, and Transgender) as a human unnaturalness. This article also seeks to reveal how the fundamental differences between Pancasila and Hadith in responding to LGBT as well as our attitude towards LGBT people in the current context. This research is a library research with data analysis techniques using content analysis. The data analysis technique in this research is done by collecting all materials related to LGBT through Google Scholar both in the perspective of Pancasila and Hadith. Then conducted a literature review of the content in depth. The findings are Pancasila and Hadith have the same perspective that LGBT cannot be legalized. Pancasila and Hadith limit freedom of expression and not unlimited freedom. Our attitude towards LGBT people in the context of today is to embrace, rehabilitate, and provide education, not to judge, discriminate, and segregate them.